Bimetallic Mo–Co nanoparticles anchored on nitrogen-doped carbon for enhanced electrochemical nitrogen fixation. Issue 18 (27th April 2020) - Zhang, Yizhen; Hu, Jue; Zhang, Chengxu; Liu, Yizhe; Xu, Mengyuan; Xue, Yujia; Liu, Lifen; Leung, Michael K. H.
Abstract : The Mo–Co bimetallic nanoparticles anchored on the nitrogen-doped porous carbon (Mo–Co/NC) are developed and serve as a cost-effective catalyst candidate for the NRR. Abstract : Electrocatalytic nitrogen fixation at room temperature and ambient pressure is considered to be one of the most energy-efficient and environmentally-friendly approaches to ammonia (NH3 ) production. The construction of efficient catalysts for the electrocatalytic nitrogen reduction reaction (NRR) remains a significant challenge. However, there have been no reports dedicated to non-noble bimetals on nitrogen-doped carbons as efficient NRR electrocatalysts, considered from either side of the theoretical volcano plot for the NRR. Herein, Mo–Co bimetallic nanoparticles anchored on nitrogen-doped porous carbon (Mo–Co/NC) are developed for the first time and serve as a cost-effective catalyst candidate for the NRR. In comparison to single-metallic Co/NC, a bimetallic Mo–Co/NC catalyst exhibits the enhanced activity and selectivity of NRR electrocatalysis with an ammonia yield of 89.8 μmol h −1 gcat. −1 and a faradaic efficiency of 13.5%, at a low operating potential of −0.10 V ( vs. RHE) in 0.1 M Na2 SO4 . Moreover, the composite catalyst shows high electrochemical stability and selectivity during 50 000 s of NRR processing. The favorable NRR electrocatalytic activity of Mo–Co/NC could be ascribed to the synergistic effect of strongly adsorbed Mo and weakly adsorbed Co composite. This work provides a facile strategy towards the design of porous non-precious metallic electrocatalysts for efficient NRR under ambient conditions.